The influence of venture capital on growth through innovation and the use of internet technology in Micro and Small Industries (MSIs) in Indonesia - Myrna Sofia; Firwan Tan; Nasri Bachtiar; Febriandi Prima Putra (Economies, 2022)
One challenge that Micro and Small Industries (MSIs) face is financing. Venture capital is one of the financing options to overcome capital problems by providing financial and non-financial support. This study aims to analyze the influence of venture capital on the growth of Micro and Small Industries (MSIs) in Indonesia through innovation and internet technology as the intervening variables. The research data were collected from a survey (Statistics Indonesia) in 2019 with 83,616 Micro and Small Industries (MSIs) as the samples. This research used the STATA logistic regression method and the Sobel test. The results showed that venture capital had a direct positive but insignificant influence on growth. Meanwhile, innovation could mediate the effect of venture capital on growth, yet the use of internet technology could not mediate the impact of venture capital on growth. This study proves that venture capital increases innovation activities and accelerates growth.
Keywords: 330; growth; innovation; use of internet technology; venture capital